Sensory traits, color, and shelf life of low-dose irradiated beef steaks - S.E. Luchsinger; Donald H. Kropf; C.M. Garc a Zepeda; James L. Marsden; Melvin C. Hunt; M.E. Hollingsworth; Sally L. Stroda; Edgar Chambers; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1996)
Irradiation had minimal effects on flavor and texture of frozen or chilled vacuum-packaged boneless beef steaks. A dose level of 3.5 kilograys (kGy) reduced beef aroma in chilled steaks. Irradiation did not influence internal or external cooked color, most raw color traits, cooking loss, pH, oxidative rancidity, or Warner-Bratzler shear force in chilled or frozen boneless steaks. PVC-wrapped controls were less red than irradiated steaks after 5 days of display. Exposure to oxygen by repackaging into oxygen-permeable film increased oxidative rancidity after display. Vacuum-packaging, in combination with irradiation, enables boneless beef steaks to be stored and/or displayed up to 28 days with minimal effects on color, oxidative rancidity, and bacterial counts.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Irradiation; Beef steaks; Sensory; Color